2013
DOI: 10.1111/jch.12084
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma/Paraganglioma: Review of Perioperative Management of Blood Pressure and Update on Genetic Mutations Associated With Pheochromocytoma

Abstract: Pheochromocytomas and paragangliomas are rare tumors with high morbidity, due to excessive catecholamine secretion, even though the majority of tumors are benign. The use of perioperative blockade regimens, together with improved surgical techniques, has greatly impacted the perioperative morbidity associated with these tumors. The old dogma of the “tumor of tens” no longer holds true. For example, at least one-third of all pheochromocytomas and paragangliomas are hereditary with mutations in one of ten well c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 46 publications
0
66
0
7
Order By: Relevance
“…17,18 While practices in preparation for surgical treatment of malignant PHEOS vary at each institution, we recognize that recent research and review articles suggest that metyrosine is ideally used in combination with alpha blockade, including either competitive or non-competitive agents. 10,11,13 Still, a review of older reports suggests that metyrosine monotherapy is a suitable option for achieving perioperative BP control in both malignant and benign PHEOS. 7 Although one case report indicated that metyrosine had not been effective as a sole agent, 15 similar reports exist for phenoxybenzamine monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 While practices in preparation for surgical treatment of malignant PHEOS vary at each institution, we recognize that recent research and review articles suggest that metyrosine is ideally used in combination with alpha blockade, including either competitive or non-competitive agents. 10,11,13 Still, a review of older reports suggests that metyrosine monotherapy is a suitable option for achieving perioperative BP control in both malignant and benign PHEOS. 7 Although one case report indicated that metyrosine had not been effective as a sole agent, 15 similar reports exist for phenoxybenzamine monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As alternative forms of alpha-1 blockade are competitive antagonists, any catecholamine surges resulting from tumour manipulation during resection could displace the drug from the receptor and increase the risk for hypertensive crisis. 9,11 In many studies, metyrosine has been used concomitantly with alpha-1 blockade-primarily phenoxybenzamine-in the preoperative management of PHEOS. In retrospective studies, this combination of metyrosine and alpha blockade has been associated with resections that required less volume and pressure control compared with the classical method of single-agent adrenergic blockade.…”
Section: Discussionmentioning
confidence: 99%
“…A paragangliomák mintegy 85%-a a hasüregben található, elsősorban a juxtarenalis és paraaorticus régió-ban. A phaeochromocytomák 10-15%-a, míg a paragangliomák 30-50%-a malignus [1][2][3][4]. Jellegzetes eltérés észlelhető a hormontermelésben is.…”
Section: Esetismertetésunclassified
“…For example, the analysis of catecholamine in blood is important for monitoring the normal and pathological activity of the adrenal gland [131,132]. The HPLC and CE quantification of catecholamine in plasma is a significant marker for some diseases such as pheochromocytoma and hypertension [133,134]. On the other hand, other central nervous system (CNS) stimulants such as caffeine and theobromine existing in tea, cocoa and coffee are also used in respiratory disorders as bronchodilators present in many pharmaceutical preparations.…”
Section: Swcnts and Mwcnts For Achiral Separation Of Pharmaceuticals mentioning
confidence: 99%